Autologous stem cell transplantation outcomes in elderly patients with B cell Non‐Hodgkin Lymphoma. (26th June 2015) - Gohil, Satyen H.; Ardeshna, Kirit M.; Lambert, Jonathan M.; Pule, Martin A.; Mohamedbhai, Sajir; Virchis, Andres; Morris, Emma C.; Linch, David C.; Thomson, Kirsty J.; Peggs, Karl S.
Summary The precise role of autologous haematopoietic stem cell transplantation (ASCT) remains unclear in patients over 60 years of age. There is potential for increased procedural morbidity and mortality, and differences in disease biology that could impact outcomes. We performed a retrospective single‐centre review of 81 elderly B‐cell Non‐Hodgkin Lymphoma patients undergoing ASCT. Five‐year overall survival (OS) and progression‐free survival (PFS) was 54·7% and 49·1% respectively. Non‐relapse mortality (NRM) at 100 days and 1 year was 1·3% and 2·5%, suggesting no major excess compared to younger cohorts. OS and PFS were significantly worse in those over 65 years compared to those aged 60–64 (47·6% vs. 57·7%, P = 0·0437, and 27·6% vs. 57·7%, P = 0·0052 at 5 years). This resulted largely from an increased relapse risk (RR) (53·8% vs. 30·1%, P = 0·0511) rather than excess NRM, and age remained independently significant for PFS on multivariate analyses [Hazard ratio 2·56 (1·35–4·84, P = 0·0052) for PFS and 1·89 (0·99–3·61, P = 0·054) for OS]. Our data adds to the growing body of evidence demonstrating that ASCT can be an effective treatment strategy with an acceptable safety profile in selected elderly patients. Further evaluation of its overall benefit is warranted, however, in those over 65 years of age, as RR appears to be considerably higher.